A Novel Approach for Qualitative Imaging of Buried PEC Scatterers - Martina Teresa Bevacqua (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
A new linear approach for support reconstruction of impenetrable objects is described and tested in case of scattered field data collected in Ground Penetrating Radar measurement configuration. Starting from the considerations that in high conductivity scatterers the currents induced inside the scatterers are only localized on its boundary and that they take up only few pixels of the entire investigation domain, a sparsity promoting inversion technique is formulated. The flexibility of the approach allows to counteract the specific difficulty to work under “aspect limited” measurement configurations, as the one at hand. Examples with numerical noisy data are given to demonstrate and validate the effectiveness of the method in localizing and in retrieving the shape of the unknown objects buried in lossy soil.